Exploring the Characteristic Features of the Language of Science and Technology - Dirgeyasa, I Wy. (Universitas Negeri Semarang, 2024)
It is a fact that in the last few years the science and technology have developed rapidly and widely across the world. Their development has brought a number of positive and significant impacts for human life such as easy transportation, wide and various job opportunity, working mechanization and automation, longer life span, etc. But in order to sustainably and widely development and implement the science and technology, human beings must understand and master the language of the science and technology proficiently. Nevertheless, many students, scholars, academicians, researchers, even scientists find hard to understand and master the language of science and technology well. This paper attempts at exploring the nature of language of science and technology, the characteristic features, and the historical development of the language and science across time.